The Husseini Narrative in Karbala: From Historical Formation to Poetic Representation/ السردية الحسينية في كربلاء: من التشكُّل التاريخي إلى التمثُّل الشعري - Akssam Ahmed Fayad; Anwar Saeed Jawad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study seeks to explore the Husayni narrative as a grand, transhistorical narrative rooted in the event of Karbala and extending its influence across history, cultures, and the Shiʿi, Islamic, and broader human collective consciousness. In its theoretical section, the research examines the concept of “narrative” through critical grounding and analysis, elucidating how grand narratives are formed within historical, symbolic, and religious structures. It then investigates the extent to which the essential components of such a narrative are fulfilled in the Husayni cause, drawing on modern narrative theories, pragmatic linguistics, and poetic analysis.The applied section analyzes selected examples of Karbala poetry that reconstruct collective memory and intensify the dimensions of the Husayni narrative within an aesthetic literary framework, wherein the voices of the victim, history, and the oppressed community converge. This analysis is grounded in a deep pragmatic and interpretive approach.The study concludes that the Husayni narrative is not merely a tragic story, but rather an “open symbolic system” that embraces values of dignity, resistance, and moral integrity in opposition to injustice and oblivion. Accordingly, it is a narrative capable of renewal, transmission, and functional reappropriation across generations.